Liquiritin elicitation can increase the content of medicinally important glucosinolates and phenolic compounds in Chinese kale plants. (21st December 2019) - Akram, Waheed; Saeed, Taiba; Ahmad, Aqeel; Yasin, Nasim A; Akbar, Muhammad; Khan, Waheed U; Ahmed, Shakeel; Guo, Juxian; Luo, Wenlong; Wu, Tingquan; Li, Guihua
Abstract: BACKGROUND: Brassica oleracea var. alboglabra (Chinese kale) is an important vegetable grown in southern China. This study was aimed at searching for environmentally friendly and affordable approaches to increase the production of medicinally relevant glucosinolates and phenolic compounds in Chinese kale plants. For this purpose, the foliar application of liquiritin at 0 (control), 250, 500 and 750 ppm was tested starting from the four‐leaf stage and repeated every two weeks until plants were two months old. RESULTS: Foliar application of liquiritin in Chinese kale plants significantly increased glucosinolates and total phenolic content, in a dose‐dependent manner. Compared with control plants, 2.3‐ and 1.9‐fold increases in yields of glucosinolates and total phenolic content, respectively, were corroborated in Chinese kale plants treated with 750 ppm of liquiritin. Along with rises in the content of eight different glucosinolates, liquiritin elicitation effectively increased the concentration of glycosilated and acylated flavonoids and hydroxycinnamic acids. The expression of genes involved in glucosinolate and phenolic biosynthesis was significantly higher in liquiritin‐treated plants as compared to controls. CONCLUSIONS: Liquiritin elicitation is a feasible and environmentally friendly practice for increasing the production of medicinally important glucosinolates and phenolic compounds in Chinese kale, which may improve this plant's value as a nutraceutical food. This study also contributes to understanding the molecular mechanisms underlying liquiritin elicitation. This is the first report documenting the use of liquiritin for an elicitation purpose in plants. © 2019 Society of Chemical Industry